Urdu as Medium of Instruction in Professional Institutions - Haque, Anwar Ul (International Journal of Pathology, 2019)
Some may go into shock seeing this title of our editorial. What a silly idea, what a stupid thought, how can we live in “stone age.” (If there was indeed such an age.) I remember during my medical college days at Dow Medical College, in one departmental test (stage) I described the boundaries of femoral triangle in Urdu; that sent my demonstrator teacher into disbelief; what are you saying. I was amazed as I was describing the boundaries accurately, but he couldn’t digest it because it was in Urdu. Later after many years I was invited to give a talk on post-splenectomy septicemia based on my original research on Sprague Dawley rats, as I began in Urdu, one well-wisher doctor came on the stage and whispered in my ears; “Please don’t do, what people will think, give lecture in English.” Unfortunately, I had to comply with his absurd idea.